EFFECTS OF ECOLOGICAL DESIGN SYSTEMS ON SUSTAINABLE ENVIRONMENTAL CONSERVATION OF TEA FACTORIES IN NANDI COUNTY - Maluki, Clinton; Keitany, Pauline (International Journal of Supply Chain Management, 2021)
Purpose: The main purpose of this study was to examine the effects of ecological design systems on sustainable environmental conservation of tea factories in Nandi County. The study was guided by transaction economic cost theory. Methodology: The study used explanatory research design to help in exploring research questions with varying levels of depth. A semi-structured questionnaire with Likert-type interval scale anchored on a five-point scale was used to collect primary data. A pilot study was conducted in Eldoret Kiptagich tea wholesalers to test the validity of research instrument, Cronbach's alpha formular was used to test reliability. The analysis technique included both descriptive statistics (means, standard deviation, percentages & frequencies) and inferential which included multiple regression analysis conducted at 95% confidence level with significance levels of 0.05. Data has been presented in tabular format. Findings: The findings of the study indicated that ecological design practices had positive and significant influence on sustainable environmental conservation of tea factories in Nandi county (Î² =0.113; p<0.05). The study concluded that ecological design, reverse logistics, green production and green procurement are the predictors of sustainable environmental conservation of tea factories in Nandi county. The study recommends that more participation of national government on implementation of sustainable environmental conservation is necessary to ensure that the future generation is well taken care of by ensuring the four-bottom line of sustainable supply chain are practiced. The study also recommends tea processing firms and other manufacturing firms adopt GSCM practices in their supply chain operations. The study suggests that further studies should be conducted in processing firms other than tea processing firms. Unique contribution to theory, practice and policy: Further studies can be conducted to relate GSCM with individual aspects of performance such as Economic, Environmental and Social and future other replica studies can be done on the areas of ecological design on sustainable performance.